ANALISIS PERLINDUNGAN HUKUM JAMAAH UMRAH DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH PADA PT. BIMA TOUR MAKASSAR - Fathur Rahman; M. Hasibuddin; Nur Setiawati; Hasanna Lawang; Subaedah Subaedah; Bahrur Rahman Hasba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the increasing public interest in performing the Umrah pilgrimage, which has been accompanied by the rapid growth of Umrah Travel Organizers (Penyelenggara Perjalanan Ibadah Umrah / PPIU) and several cases of legal protection abuse involving pilgrims, including the First Travel and Abu Tours cases. This study aims to examine the impact of the abuse of legal protection on the pilgrims of PT. Bima Tour and to analyze the legal protection provided from the perspective of Islamic economic law. A qualitative method with a case study approach was employed. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that no actual cases of legal protection abuse causing losses to the pilgrims of PT. Bima Tour were identified, either in terms of financial loss, fulfillment of pilgrims’ rights, departure schedules, safety, or trust. However, a potential risk was found due to the absence of written Standard Operating Procedures (SOPs) for handling customer complaints. From the perspective of Islamic economic law, the legal relationship between PT. Bima Tour and its pilgrims is based on the wakalah bil ujrah contract, which complies with the principles of justice ('adl), trustworthiness (amanah), honesty (shiddiq), mutual consent (ridha), and is free from gharar. Nevertheless, transparency regarding travel insurance information still requires improvement. Overall, the legal protection provided by PT. Bima Tour is generally consistent with the principles of Islamic economic law.